Assessment of the Process of Epithelialization After Complex Treatment of Diabetic Foot Syndrome - Ergashev Ulugbek Yusufjanovich; Abdusalomov Bekzod Alisher ogli; Zokhirov Adhamjon Rafiqovich; Ernazarov Khojimurod Irsalievich; Minavarxujaev Ravshanxuja Rahmatxuja ogli (Zien Journals, 2023)
Currently, the treatment of diabetes mellitus and its complications remains an urgent problem. Patients with diabetic foot syndrome, a complication of diabetes mellitus, are increasingly losing their quality of life and ability to work. The treatment of diabetes mellitus and its complications affects the economic and financial efficiency of our country. Therefore, the new drug Reomannisol, produced in our country, helps to stop the purulent-necrotic process of the foot, which is a complication of diabetes mellitus
Keywords: Experimental model of diabetic foot; purulent-necrotic process; experimental animals; alloxan